FIRST REPORT IN IRAQ : AMINO ACID SUBSTITUTION IN PMRCAB GENES AND THERE CORELLATION WITH COLISTIN RESISTANCE AMONG A.BAUMANNII ISOLATES - H. S, Rusul.; S. M, Suhad. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
In the present study,out of 120 samples were collected from different clinical sites from patients who admitted to different hospitals in Baghdad city,only 65 samples were detected as A. baumannii.The antibiotics susceptibility test showed that the bacteria were resistant to piperacillin (92.31%), cefotaxime (87.69%),trimethoprimsulfamethoxazole(73.85%).While Meropenem (70.77%)and gentamycin(67.69 %).The resistance rate to imipenem and tetracycline were 58.46% and 43.08% respectively. Eventually, just(20%)among all isolates are resistant to levofloxacin. While the percentage of colistin resistance was performed among 23 isolates and the results showed that all isolates were reported resistance in a percentage 100% with MIC values ≥ 16 µg/100µl.The results of pmrCAB genes detection and sequencing among seven A.baumannii isolates, which were choices because they were resistant to all antibiotics even colistin, were showed that the entire region of the pmrC containing fourteen missense mutations. Out of twelve detected mutations in pmrA, only one of them was found to exhibit a missense mutations. While the results of pmrB gene showed three missenses mutations.